PRICE DISCOUNT VERSUS FREE SHIPPING: COMPARING PROMOTIONAL EFFECTIVENESS AMONG GENERATION Z TIKTOK SHOP USERS - Ari Raharjo; Tety Elida; Keysha Fatiha Fausyam; Zahra Orchidiella Hanum (Universitas Gunadarma, 2026)
This study examines the effects of price discounts and free shipping on the purchase intention of Generation Z consumers using TikTok Shop in Indonesia. It also compares the relative effectiveness of these two promotional strategies in stimulating purchase intention within a social commerce environment. A quantitative explanatory research design was employed. Data were collected through an online questionnaire administered to Generation Z TikTok Shop users selected using purposive sampling. The research model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with RStudio. The measurement model was evaluated through validity and reliability tests, while the structural model was assessed using path coefficients, bootstrapping, effect sizes, and comparative analysis.The results reveal that both price discounts and free shipping have positive and significant effects on purchase intention. However, free shipping demonstrates a stronger influence than price discounts, indicating that eliminating shipping costs is more effective in reducing consumers’ psychological barriers during the purchasing process. The findings suggest that minimizing transaction friction is more influential than conventional price reductions in encouraging purchase intention among Generation Z consumers. This study extends the social commerce literature by directly comparing the effectiveness of price discounts and free shipping within a single analytical model.